Impact of Drought on Chemical Composition and Sugar Yields From Dilute-Acid Pretreatment and Enzymatic Hydrolysis of Miscanthus, a Tall Fescue Mixture, and Switchgrass - Hoover, Amber; Emerson, Rachel; Ray, Allison; Stevens, Daniel; Morgan, Sabrina; Cortez, Marnie; Kallenbach, Robert; Sousek, Matthew; Farris, Rodney; Daubaras, Dayna (Frontiers in Energy Research, 2018)
Environmental factors like drought impact the quality of biomass entering a bioconversion process. Drought often reduces the sugar content in lignocellulosic biomass, which could have economic impacts, particularly when compounded with losses in dry biomass yield; however, the effects on conversion efficiency are not completely understood. This study investigated how drought may impact biomass composition and sugar yields from dilute-acid pretreatment and enzymatic hydrolysis of Miscanthus, a tall fescue mixture, and switchgrass from Nebraska, Missouri, and Oklahoma, respectively, grown as part of Regional Feedstock Partnership field trials. Samples were grown and harvested in 2010 during non-drought conditions and in 2012 during extreme drought conditions. Non-structural glucose and proline were significantly greater in 2012 compared with 2010 for Miscanthus, which suggests drought stress occurred. Structural glucan and xylan were significantly decreased in 2012 for Miscanthus; however, reactivity and sugar yields from dilute-acid pretreatment and enzymatic hydrolysis were significantly greater in 2012 compared with 2010, suggesting that although structural sugars may decrease during drought conditions, sugar yields and reactivity may increase. For the tall fescue mixture, proline was greater, and structural sugars were lower in 2012, indicating drought stress, but minimal differences were observed in the conversion experiments. Few differences were observed for switchgrass composition and reactivity between years. The observed patterns are likely because of site-specific climatic conditions combined with the tolerance each species may have to drought. As drought occurrence and severity have increased, it is necessary to understand drought impacts to mitigate risks to future bioenergy industry growth.